2013
DOI: 10.3349/ymj.2013.54.1.154
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications and Risk Factors of Acute Pancreatitis after Cardiac Valve Surgery

Abstract: PurposeAcute pancreatitis is one of the potentially lethal complications that occurs after cardiac surgery. We tried to identify risk factors for and the prognosis of acute pancreatitis after cardiac valve surgery with cardiopulmonary bypass.Materials and MethodsWe retrospectively analyzed a database of consecutive patients who underwent cardiac valve surgery with cardiopulmonary bypass between January 2005 and April 2010 at our institution. Patients were classified as having acute pancreatitis based on serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…An increase in aortic clamping time may lead to low cardiac output and/or release of inflammatory mediators[ 10 ]. In addition, if CABG is combined with valve surgery, the risk of mesenteric embolism increases[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in aortic clamping time may lead to low cardiac output and/or release of inflammatory mediators[ 10 ]. In addition, if CABG is combined with valve surgery, the risk of mesenteric embolism increases[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of studies reported by Perez et al (7), AP secondary to CABG surgery leads to longer postoperative length of stay and greater in-hospital mortality than patients who do not develop pancreatitis. Also, AP has been shown to have high mortality after cardiac valve replacement surgery (8). Hyperamylasemia is not always specific for AP, so the discrimination between postoperative acute pancreatitis and hyperamylasemia is important in CABG surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found only one article focusing solely on rates and risk factors of acute pancreatitis. 10 This study by Chung et al focused strictly on patients after valve replacement and yielded relatively high rates of 5.9%, 10 compared with a study by Marsoner et al, with an overall rate of 0.84%. 3 The significant difference could be explained by lower serum marker threshold for diagnosis in the paper by Chung et al, as neither of the studies required patients to have abdominal pain for diagnosis.…”
Section: Acute Pancreatitismentioning
confidence: 97%
“…3 10 Patients who suffered acute pancreatitis after cardiac surgery had a mortality of 0%-15.5%, 3 10 and an extended hospital stay. 10 The average time from index cardiac operation to diagnosis was 9 days. 3 The criteria for diagnosis of acute pancreatitis varied and included lipase of >180 U/L, lipase of more than three times the patient's baseline or >60 U/L if the patient had concurrent abdominal pain, 10 or leukocytosis and elevated lipase >300 U/L regardless of the presence of abdominal pain.…”
Section: Acute Pancreatitismentioning
confidence: 99%